Correlation of TL layers for the synchronous paleoceanographic events in the East Sea (Sea of Japan) during the Late Quaternary - Khim, Boo-Keun; Tada, Ryuji; Park, Yu Hyeon; Bahk, Jang Jun; Kido, Yoshiki; Itaki, Takuya; Ikehara, Ken (Geosciences journal (Seoul, Korea), 2009)
TL layers (i.e., dark mud layers), either thin or thick, as determined by the L* values with lithologic observation, are distinct paleoceanographic signatures in the East Sea (Sea of Japan), which were formed in response to the global eustatic sealevel fluctuations between interglacials and glacials during the Late Quaternary. These lithologic markers were consistently correlated among the three sediment cores (MD01-2407, 05GCRP21, and KR05-09PC1) collected from the Oki Ridge of the southern Yamato Basin, the South Korea Plateau of the northern Ulleung Basin, and the Matsumae Plateau of the northeastern Japan Basin, respectively. Reconstruction of age models for cores 05GCRP and KR05-09PC1 was aided in a good way by the AMS 14 C ages of planktonic foraminifera and identification of the tephra layers, and mainly by lithostratigraphic correlation with TL layers of well-dated core MD01-2407, based on the L* values. The correlation of TL layers among the three sediment cores was remarkable, indicating that the East Sea (Sea of Japan) experienced the synchronous and basin-wide scale paleoceanographic events during the Late Quaternary. Our study exemplifies the significant usefulness of these lithologic markers for further Late Quaternary paleoceanographic investigation.